Effectiveness And Role Of The Food Duty Unit Of Police Region Of Central Java In Law Enforcement In The Field Of Food In The Regional Law Of POLDA Central Java - Anggrin Gayuh Praptiwi; Lathifah Hanim (Jurnal Daulat Hukum, 2019)
The problems of this study are:effectiveness and the role of the task force food Central Java Police in law enforcement in the food sector in the jurisdiction of the Central Java Police to current and factors that influence the effectiveness of law enforcement in the food sector in the jurisdiction of the Central Java Police to current and effectiveness and role food task force in law enforcement in the food sector in the Indonesian National Police.The method used by researchers approach juridical law and specification in this study were included descriptive analysis. The sources and types of data in this study are primary data obtained from interviews with field studies Kasubdit 1 Indagsi Ditreskrimsus Central Java Police, And secondary data obtained from the study of literature relating to the theory of law and law enforcement effectiveness.Based on the results of research that doing the duties and responsibilities of everyday office designated as the task force to conduct law enforcement, and improve the system in the handling of cases of food mafia that is still public concern with the following activities: monitoring the price and distribution of food; minimize the actions of speculators; monitor the potential emergence of cartel practices; prosecution of activities that are hoarding staple; Another prosecution of illegal activity related to food (mixing / deviation fertilizer, iodine salt is below standard, refined sugar, cooking oil used, etc.). Factors that influence the effectiveness of law enforcement in the field of food in the region of Central Java regional police law in force at the moment is the legal structure factor, the factor of the substantive law and legal culture factor. The effectiveness and the role of food in law enforcement task force in the food sector in the Indonesian National Police monitoring the prices of basic commodities in the markets and the results were evaluated every two weeks. The evaluation will be conducted to measure the effectiveness and benefits of the role of the Food Task Force.Keywords : Effectiveness; Role; Food Task Force; Law Enforcement